P2X 7-receptor binding in new-onset and secondary progressive MS – a [11C]SMW139 PET study - Lehto, Jussi; Aarnio, Richard; Tuisku, Jouni; Sucksdorff, Marcus; Koivumäki, Esa Mikko; Nylund, Marjo; Helin, Semi; Rajander, Johan; Danon, Jonathan; Gilchrist, Jayson; Kassiou, Michael; Oikonen, Vesa; et al. (Springer Nature, 2025)
Background
PET imaging of activated microglia has improved our understanding of the pathology behind disability progression in MS, and pro-inflammatory microglia at ‘smoldering’ lesion rims have been implicated as drivers of disability progression. The P2X 7R is upregulated in the cellular membranes of activated microglia. A single-tissue dual-input model was applied to quantify P2X 7R binding in the normal appearing white matter, perilesional areas and thalamus among progressive MS patients, healthy controls and newly diagnosed relapsing MS patients.
Results
Overall, tracer uptake in the MS brain was not significantly higher compared to HCs. In the 3 mm perilesional rim of all T1 lesions, tracer binding was higher among relapsing patients compared to progressive patients. Tracer binding was higher in males compared to females. Disease duration correlated with tracer binding in the normal appearing white matter. Age correlated negatively with tracer binding in the perilesional rims.
Conclusions
Even as binding estimates obtained with the dual-input model were consistent with the expected distribution of P2X 7Rs in the MS brain, the small free fraction of the parent tracer may limit its accuracy and applicability, and binding estimates between subjects were highly variable. Conclusive evidence for the applicability of [11C]SMW139 to detect MS-related diffuse smoldering inflammation was not obtained.